Life Skill Dan Keharusan Penataan Kembali Pendidikan Indonesia - Toharuddin, Toharuddin (ULUL ALBAB Jurnal Studi Islam, 2003)
General Life Skill is a set of skills which is needed by those who are either already working or still studying. General Life Skill (GLS) comprises personal skill which consists of self-awareness and rational thinking and social skills. In Life Skill concept, this general life skill is prioritized to be developed. The problem is, in the practice of education, it is often "neglected" The education often gives less consideration to the process of emotional development (self-awareness), and method of rational thinking and even there is a tendency of education to act as an elite institution which is unfriendly to its social environment.